Genesis of sources of legal regulation of relations in the provision of hotel services - Achilova, Liliya (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The zone of dynamic development of applied science and industry is a technology park that creates the most favorable conditions forbusiness and provides an opportunity to use research, design and application of new digital technologies. The main goal of creating innovation centers is to create favorable conditions for the formation and development of digital technologies. This is based on the effective use of information and communication technologies, scientific and educational integration and industrial integration